Sensacyjny charakter informacji naukowej w przekazach popularnonaukowych i upowszechniających wiedzę - Starzec, Anna (Stylistyka, 2019)
The main field of interest is the sensational character of texts with scientific subject matter. This is a characteristic trait of potentially every field of social life and almost every type of discourse, but in popular science texts and texts popularizing scientific knowledge it is presented in a more balanced way. On the basis of many examples of texts presented in online information portals the author shows how variously journalists value scientific discoveries and how this opinion depends on the evaluation of the scientific circles. In conclusion, it might be stated that the sensational character, so inseparably connected with tabloids, differs from the sensational character of popular science texts and texts popularizing scientific knowledge.